2017
DOI: 10.4315/0362-028x.jfp-17-097
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Salmonellosis from Chicken Parts Prepared from Whole Chickens Sold in Flow Pack Wrappers and Subjected to Temperature Abuse

Abstract: The flow pack wrapper is a popular packaging choice for retail sale of whole chickens. However, it may provide a favorable environment for growth and spread of Salmonella within the package, leading to an outbreak of salmonellosis. To investigate this possibility, a process risk model was developed that predicted the risk of salmonellosis from chicken parts prepared from whole chickens sold in flow pack wrappers and subjected to proper storage (6 h at 4°C) or improper storage (72 h at 15°C) before preparation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Therefore, to provide a better simulation of dose-response, a model (i.e. disease triangle, dose-response model) that is based on outbreak and human feeding trial data and that produces nonsigmoid-shaped dose-response curves and that considers differences in virulence among serotypes of Salmonella, differences in food factors and difference in resistance among consumers was modified and used in the present study (Oscar 2017b). Another common approach in process risk modelling is to express dose-response as a probability of illness (Straver et al 2007;Smadi and Sargeant 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to provide a better simulation of dose-response, a model (i.e. disease triangle, dose-response model) that is based on outbreak and human feeding trial data and that produces nonsigmoid-shaped dose-response curves and that considers differences in virulence among serotypes of Salmonella, differences in food factors and difference in resistance among consumers was modified and used in the present study (Oscar 2017b). Another common approach in process risk modelling is to express dose-response as a probability of illness (Straver et al 2007;Smadi and Sargeant 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Samples for qPCR were collected at 6 h of WSE in 400 ml of BPW incubated at 40°C and 80 rev min À1 . The standard curve had an enumeration range from 0 to 4Á24 log or 1 to 17 348 per 25 g. The standard curve was developed with Salmonella serotypes Newport, Kentucky, and 8,20:-:z 6 , which were isolated from chicken parts in previous studies (Oscar 2013(Oscar , 2014(Oscar , 2017b, and with serotype Infantis, which was isolated from GC in the present study. The highest C T values at each dose of Salmonella were used to develop the standard curve and provided a conservative (fail-safe) estimate of log number as explained and justified in previous studies (Oscar 2014(Oscar , 2017b.…”
Section: Data Collectionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cross‐contamination of RTE salad vegetables with Salmonella from raw chicken followed by growth during meal preparation are important risk factors for human salmonellosis. Oscar () quantified natural cross‐contamination of RTE cooked chicken with Salmonella from raw chicken during simulated meal preparation. When raw chicken was properly stored (6 hr at 4°C) before meal preparation, 10% of RTE cooked chicken portions were cross‐contaminated with low (0–0.2 log) numbers of Salmonella from unwashed utensils (i.e., cutting board, knife, and hands) used to prepare raw chicken for cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Oscar () also quantified natural cross‐contamination of RTE cooked chicken with Salmonella from raw chicken that was improperly stored (72 hr at 15°C) before meal preparation. He found that 52% of RTE cooked chicken portions were cross‐contaminated with 0.3–6.2 log of Salmonella from unwashed utensils used to prepare raw chicken for cooking.…”
Section: Discussionmentioning
confidence: 99%